2001
DOI: 10.1063/1.1336560
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of deep levels in semi-insulating GaAs by means of the temperature change piezoelectric photo-thermal measurements

Abstract: Articles you may be interested inBroadening effects and ergodicity in deep level photothermal spectroscopy of defect states in semi-insulating GaAs: A combined temperature-, pulse-rate-, and time-domain study of defect state kinetics Investigation of the annealing effect on the nonradiative carrier recombination in AlGaAs/GaAs utilizing the piezoelectric photothermal technique Rev. Sci. Instrum. 74, 550 (2003); 10.1063/1.1515888 Field-enhanced trapping in deep levels by multiple phonon emission in semi-insulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…We, therefore, propose on electron generation and recombination dynamics to explain the peak at 150 K in the temperature variation of the PPT signals, based on the model proposed in our previous paper. 1) In this model, the Ni deep level acts as both the source of the thermal excitation of free carriers (electron) to the conduction band and the sink for the electrons caputured from the conduction band. Since the probing-light wavelength of 1376 nm has a photon energy of 0.9 eV, which is lower than the band gap energy of Si (1.16 eV at 100 K), we propose that the carriers are optically excited from certain level(s) other than that of the Ni acceptor in the band gap of Si.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We, therefore, propose on electron generation and recombination dynamics to explain the peak at 150 K in the temperature variation of the PPT signals, based on the model proposed in our previous paper. 1) In this model, the Ni deep level acts as both the source of the thermal excitation of free carriers (electron) to the conduction band and the sink for the electrons caputured from the conduction band. Since the probing-light wavelength of 1376 nm has a photon energy of 0.9 eV, which is lower than the band gap energy of Si (1.16 eV at 100 K), we propose that the carriers are optically excited from certain level(s) other than that of the Ni acceptor in the band gap of Si.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that activation energies, concentrations and the capture cross sections of deep defect levels in semi-insulating GaAs such as EL6, EL7, and EL15 were fully investigated by examining the temperature variation of the piezoelectric photothermal (PPT) signals. 1) The great advantage of this technique is that this is a direct monitor of the nonradiative recombination process that is a major process effecting the deep levels. Heat generated by the nonradiative recombination of photoexcited electrons is detected by a piezoelectric transducer (PZT) directly attached to the rear surface of a sample.…”
Section: Introductionmentioning
confidence: 99%
“…Defect states identified in Table II are also consistent with independent measurements on the same SI-GaAs wafer. 40 Using the piezoelectric photothermal ͑PPT͒ technique, 41 Ikari and Fukuyama identified defects from HL3 to EL6. However, the defect state characteristic temperatures in the PPT spectrum are much lower than those in the DLPTS spectrum.…”
Section: -7mentioning
confidence: 99%
“…The 1.5 m laser, which represents the onset wavelength of EL2 absorption, 43 limits the absorption from EL2 level and enables proper identification of other shallower defects. Also, since the EL2 level is known to be a source of photoexcited electrons, 41 using a laser with high EL2 absorption will induce significant interband carrier transportations, which will disturb the carrier distribution generated by the 830 nm laser and make theoretical analysis to be more complicated.…”
Section: -7mentioning
confidence: 99%
“…3. The expected relevant Fermi level regime for the occurrence of a negative peak lies sufficiently above the EL2 ++/+ level (E C + 0.54 eV) [15,16] so that it is filled and its contributions can be neglected. Additionally, a recombination center was used to account for the short lifetime (&10 -9 s) [5] in the material.…”
Section: The Rate Equation Systemmentioning
confidence: 99%